Hukum Fidyah bagi Wanita yang Memakai Masker Saat Ihram pada Masa Pandemi (Analisis Fatwa Majelis Ulama IndonesiaNo. 3 Tahun 2020) - Natasha Rizqi Arifah; Rachmat bin Badani Tempo; Rahmayani Lancang (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to find out and understand the considerations and decisions of the Indonesian Ulama Council (MUI) regarding wearing masks during ihram related to the fidyah law for women on this issue. This research uses descriptive qualitative research which refers to qualitative data described descriptively. By using normative, phenomenological, and conceptual approaches. The results of the research found are as follows: First, fidyah is a ransom or a substitute for a lack of worship, either because it leaves the obligation in worship or has committed violations in it which are specifically committed during fasting and pilgrimage. Second, amid the outbreak of the Covid 19 outbreak and in order to maintain the health of the pilgrims and prevent transmission of the disease, the MUI issued a fatwa that it is permissible for women to wear face coverings or masks when in an emergency or urgent need such as transmission of dangerous diseases which if they do not wear masks can exacerbate health conditions. Third, according to Nawawi, although women are prohibited from covering their faces, it is permissible for them to cover their faces from the heat of the sun, cold weather, fear of slander by wearing underwear or (clothing) that is light, because a woman's private parts are all over her body except her face and palms. For women who do this because of an emergency, they are subject to fidyah to complete their pilgrimage.